Increasing Efficiency of Education in Primary Schools - Alimova Shukurjon Kamilovna (Zien Journals, 2022)
This article provides a brief overview of improving the quality of education in the primary grades, which are the most important part of education, the factors needed for students to receive a quality education, and today's education.
Keywords: primary school; education; technology; literacy